Asymmetric Gold‐Catalyzed Lactonizations in Water at Room Temperature1. (14th August 2014) - Handa, Sachin; Lippincott, Daniel J.; Aue, Donald H.; Lipshutz, Bruce H.
Abstract Asymmetric gold‐catalyzed hydrocarboxylations are reported that show broad substrate scope. The hydrophobic effect associated with in situ‐formed aqueous nanomicelles gives good to excellent ee's of product lactones. In‐flask product isolation, along with the recycling of the catalyst and the reaction medium, are combined to arrive at an especially environmentally friendly process.